Effects of plant materials, cutting positions, rooting media and IBA on rooting of Shorea leprosula (Dipterocarpacea) cuttings - Ab Shukor, Nor Aini; Liew, T. S. (Universiti Putra Malaysia Press, 1994)
Vegetative propagation by cuttings of seedlings of Shorea leprosula can be an effective, easy and economical means for raising quality planting stock. This study examined the possibility of raising planting stocks of S. leprosula from different plant materials (coppice and seedlings), cutting positions (upper tip, middle and basal), using concentrations of IBA (control, 50 pg, 100 pg, 150 pg and Seradix 3) and in rooting media (sand, paddy husk and coconut fibre). Basal cuttings of coppice gave the highest rooting percentage, 100% when treated with 100 pg IBA and grown in sand rooting medium. Analysis of variance based on survival and rooting percentages showed high significant differences (p<O.OO1) among and between the treatments. Coppice cuttings produced better root growth than seedling cuttings.